Strike‐slip tectonics and basin inversion in the Western Mediterranean: the Post‐Messinian evolution of the Alboran Sea. (16th March 2013) - Martínez‐García, P.; Comas, M.; Soto, J. I.; Lonergan, L.; Watts, A. B.
Abstract A comprehensive interpretation of single and multichannel seismic reflection profiles integrated with biostratigraphical data and log information from nearby DSDP and ODP wells has been used to constrain the late Messinian to Quaternary basin evolution of the central part of the Alboran Sea Basin. We found that deformation is heterogeneously distributed in space and time and that three major shortening phases have affected the basin as a result of convergence between the Eurasian and African plates. During the Messinian salinity crisis, significant erosion and local subsidence resulted in the formation of small, isolated, basins with shallow marine and lacustrine sedimentation. The first shortening event occurred during the Early Pliocene (ca. 5.33–4.57 Ma) along the Alboran Ridge. This was followed by a major transgression that widened the basin and was accompanied by increased sediment accumulation rates. The second, and main, phase of shortening on the Alboran Ridge took place during the Late Pliocene (ca. 3.28–2.59 Ma) as a result of thrusting and folding which was accompanied by a change in the Eurasian/African plate convergence vector from NW‐SE to WNW‐ESE. This phase also caused uplift of the southern basins and right‐lateral transtension along the WNW‐ENE Yusuf fault zone. Deformation along the Yusuf and Alboran ridges continued during the early Pleistocene (ca. 1.81–1.19 Ma) and appears to continue at the present day together with the active NNE‐SSW trending Al‐Idrisi strike‐slip fault. The Alboran Sea Basin is a region of complex interplay between sediment supply from the surrounding Betic and Rif mountains and tectonics in a zone of transpression between the converging African and European plates. The partitioning of the deformation since the Pliocene, and the resulting subsidence and uplift in the basin was partially controlled by the inherited pre‐Messinian basin geometry.